2021
DOI: 10.1038/s41598-021-86013-8
|View full text |Cite
|
Sign up to set email alerts
|

A modified cardiac triage strategy reduces door to ECG time in patients with ST elevation myocardial infarction

Abstract: Timely performing electrocardiography (ECG) is crucial for early detection of ST-elevation myocardial infarction (STEMI). For shortening door-to-ECG time, a chief complaint-based “cardiac triage” protocol comprising (1) raising alert among medical staff with bedside triage tags, and (2) immediate bedside ECG after focused history-taking was implemented at the emergency department (ED) in a single tertiary referral center. All patients diagnosed with STEMI visiting the ED between November 2017 and January 2020 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This novelty translates to several limitations that should be considered when interpreting our study result. As noted in our prior work, 42 there is population attrition from those diagnosed with STEMI to those receiving PCI as treatment. We observed that 11.1% of patients with STEMI were not treated with PCI despite it being available.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This novelty translates to several limitations that should be considered when interpreting our study result. As noted in our prior work, 42 there is population attrition from those diagnosed with STEMI to those receiving PCI as treatment. We observed that 11.1% of patients with STEMI were not treated with PCI despite it being available.…”
Section: Discussionmentioning
confidence: 63%
“…The STEMI screening is further challenged, because the majority of ED patients presenting with symptoms that could be STEMI will not have a STEMI. This makes early risk stratification, driven primarily by chief complaints, 41 , 42 subject to a high false positive screening rate suggesting that symptoms alone are not sufficient for effective screening risk stratification. 40 Chest pain has been used as a parsimonious criterion, and at times accompanied with shortness of breath (SOB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For outcome measurement, ECG time, cardiologist consultation time, cardiac catheterization laboratory (cath lab) activation time, the time the patient arrived at the cath lab, and balloon inflation time were obtained. We defined DTB time as the time from ED arrival to balloon inflation, door-to-ECG time as the time from ED arrival to completion of the first ECG, the ECG-to-consultation time as the time from completion of the first ECG to consultation with a cardiologist, the consultation-to-activation time as the time from cardiologist consultation to activation of the cath lab, the activation-to-cath lab-arrival time as the time from activation of the cath lab to the patient’s arrival in the cath lab, and the cath lab-arrival-to-balloon time as the time from the patient’s arrival in the cath lab to balloon inflation ( Figure 1 ) [ 1 , 2 , 3 , 7 , 8 , 9 , 19 ]. This study was approved by the Institutional Review Board of the Ditmanson Medical Foundation Chia-Yi Christian Hospital (CYCH-IRB 2022016).…”
Section: Methodsmentioning
confidence: 99%
“…With this aim, different strategies have been developed to reduce DTR time, including direct activation of the catheterization laboratory, completion of PCI team preparation within 20–30 min after the call, rapid data feedback, adoption of a team-based approach, and administrative support [ 12 ]. A recent study, for example, showed a 1 min improvement in DTR time by implementing a chief complaint-based “cardiac triage” protocol [ 13 ]. However, other strategies should be evaluated to achieve a reduction in DTR time.…”
Section: Introductionmentioning
confidence: 99%